(untitled) (Our Nature, 2023)
Shivapuri Nagarjun National Park (SNNP) plays an important role in global biodiversity conservation, but research based on avian diversity along elevation gradients has not been studied yet. Therefore, this study aims to explore avian diversity, its pattern, and environmental variables affecting bird species richness along elevation gradients. The point count method was carried out in the monsoon season (June and July) in 2019. Data for environmental variables including elevation, distance to settlement, distance to nearest water sources, temperature, and precipitation were assessed with respect to the feeding guild. A total of 130 species of bird belonging to 40 families and 12 orders were recorded including the Steppe eagle (endangered species) and Spiny Babbler (only endemic bird of Nepal), which indicate that SNNP supports avian diversity. Diversity indices showed diverse bird community assemblage such as the Shannon-Weiner diversity index (H’=2.65), Simpson diversity index (0.92), and evenness index E=0.94). Our study revealed insectivores were dominating among others and the order Passeriformes had the high species richness. Our observation revealed that the bird species richness was significantly greater at lower elevations than at mid and high elevations, showing a clear monotonic decline in species richness and diversity with increasing elevation. In the case of feeding guild (insectivores, omnivores, frugivores, and carnivores), most of the bird species showed a significant relationship with environmental variables (elevation, distance to settlement, distance to nearest water sources, temperature, and precipitation). It was concluded that not only environmental factors are responsible for affecting avian diversity but elevational gradients consisting of heterogeneous habitats can also play an important role in shaping avian diversity patterns.